Prediagnostic plasma testosterone, sex hormone‐binding globulin, IGF‐I and hepatocellular carcinoma: Etiological factors or risk markers?. Issue 1 (2nd August 2013) - Lukanova, Annekatrin; Becker, Susen; Hüsing, Anika; Schock, Helena; Fedirko, Veronika; Trepo, Elisabeth; Trichopoulou, Antonia; Bamia, Christina; Lagiou, Pagona; Benetou, Vassiliki; Trichopoulos, Dimitrios; Nöthlings, Ute; et al.
<x xml:space="preserve">Abstract</x> Elevated prediagnostic testosterone and insulin‐like growth factor I (IGF‐I) concentrations have been proposed to increase risk of hepatocellular carcinoma (HCC). However, the metabolism of these hormones is altered as a consequence of liver damage and they may have clinical utility as HCC risk markers. A case–control study was nested within the European Prospective Investigation into Cancer and Nutrition cohort and included 125 incident HCC cases and 247 individually matched controls. Testosterone, sex hormone‐binding globulin (SHBG) and IGF‐I were analyzed by immunoassays. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated by conditional logistic regression. The area under the receiver operating curves (AUC) was calculated to assess HCC predictive ability of the tested models. After adjustments for epidemiological variables (body mass index, smoking, ethanol intake, hepatitis and diabetes) and liver damage (a score based on albumin, bilirubin, aspartate aminotransaminase, alanine aminotransaminase, gamma‐glutamyltransferase and alkaline phosphatase concentrations), only SHBG remained significantly associated with risk [OR for top versus bottom tertile of 3.86 (1.32–11.3), ptrend = 0.009]. As a single factor SHBG had an AUC of 0.81 (0.75–0.86). A small, but significant increase in AUC was observed when SHBG was added to a model including the liver damage score and epidemiological variables (from 0.89 to 0.91, p = 0.02) and a net reclassification of 0.47% (0.45–0.48). The observed associations of HCC with prediagnostic SHBG, free testosterone and IGF‐I concentrations are in directions opposite to that expected under the etiological hypotheses. SHBG has a potential to be tested as prediagnostic risk marker for HCC. © 2013 UICC